Highly Stereoselective and Catalyst-Free Synthesis of Annulated Tetrahydropyridines by Intramolecular Imino-Diels-Alder Reaction Under Microwave Irradiation in Water - Luhr-Sierra, S (Royal Society of Chemistry, 2016)
A microwave-assisted method for the synthesis of tetracyclic tetrahydropyridines via an intramolecular imino-Diels-Alder reaction in water is reported. The reaction proceeds under catalyst-free conditions and shows excellent stereoselectivity. © 2016 The Royal Society of Chemistry.